Giant atypical lipomatous tumors of the thigh: a case series - Ipponi, Edoardo; Di Lonardo, Michele; Bechini, Elena; Cordoni, Martina; Cosseddu, Fabio; Capanna, Rodolfo; Andreani, Lorenzo (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Atypical Lipomatous Tumors (ALTs) are low-grade locally aggressive soft tissue tumors. Deep large sized ALTs of the thigh can cause significant functional impairment due to their mass effect. Surgical resection, which is the treatment of choice for these lesions, can be a though procedure, especially if the neoplasm comes in proximity with noble structures such as large sized arteries or nerves. The aim of our study is to assess risks and effectiveness of surgical resection, evaluating complications, local recurrences and post-operative functionality. Methods: We evaluated all the giant ALT (larger diameter of 10 cm or more) of the thigh that received surgery in our institution between 2017 and 2022. Each patient’s personal data and tumor size were evaluated. The quality of surgical margins was analyzed. MRI scans were performed both pre-operatively and during patients’ follow-up. Lower limb’s functional status was assessed using the MSTS score before and after surgery. Intra-operative and post-operative complications were recorded, as well as local recurrences. Results: Twentythree cases were included in our study. Tumors’ mean major diameter was 19.1cm. The mean pre-operative MSTS score was 25.9. Only one case suffered from significant post-operative complications. Only 2 of our cases (8.7%) developed a local recurrence after surgery. The mean post-operative MSTS score was 29.1 Conclusions: A careful surgical resection can be effective in treating giant ALTs of the thigh in reason of good functional outcomes, low complications risks and reasonable local recurrence rates.